Experimental Study on Nanomechanical Properties of Yunnan Red-Bed Mudstone. (7th July 2022) - Ye, Xian; Liu, Yongcai; Xue, Haibin; Li, Guo; Xing, Jin
Abstract : As a natural building material and building environment, red-bed mudstone has special engineering properties due to its special formation conditions. The engineering disaster caused by these special properties is becoming increasingly prominent. Therefore, it is of great theoretical significance and practical engineering value to study the macro- and micromechanical properties of red-bed mudstone. Nanoindentation mechanical tests are carried out on the red-bed mudstone from Chuxiong, Jingdong, and Nanhua in Yunnan. The microstructure, residual indentation morphology, and nanomechanical parameters of red-bed mudstone in different areas are compared and analyzed. The results show that the load-displacement curves can be divided into four stages, which are the compaction stage, linear elastic stage, holding stage, and unloading stage. Under the same loading and holding time conditions, sample 3 (Nanhua) has the deepest residual indentation, and SEM tests show that the damage to indentation is obvious. Sample 2 (Jingdong) has the shallowest residual indentation. The indentation morphology is complete and the size is small by SEM tests. The residual indentation depth of sample 1 (Chuxiong) is between sample 2 and sample 3. The average elastic modulus of sample 1 (Chuxiong) is 38.0 ± 2.29  GPa. The average hardness is 1.36 ± 0.42  GPa, and the fracture toughness is 0.966 ± 0.048  MPa·m 0.5 . The average elastic modulus of sample 2 (Jingdong) is 40.1 ± 2.03  GPa. The average hardness is 1.71 ± 0.35  GPa, and the fracture toughness is 1.142 ± 0.053  MPa·m 0.5 . However, the average elastic modulus of sample 3 (Nanhua) is 25.1 ± 2.53  GPa. The average hardness is 0.61 ± 0.21  GPa, and the fracture toughness is 0.507 ± 0.043  MPa·m 0.5 . Overall, the elastic modulus and the hardness of sample 2 (Jingdong) are the greatest because of its high quartz crystal content. It shows that the nanomechanical properties of red-bed mudstone in Jingdong are better than those in Chuxiong and Nanhua. The results can provide a basis for revealing the regional differences in macroscopic mechanical properties of Yunnan red-bed mudstone.